Women and rhetoric - Adams, B; Adams, Bronte (1991)
﻿ This thesis studies the ways in which female characters in Chaucer's poetry use language. Differences between feminine and masculine discourse in the Legend of Good Women and Troilus and Criseyde are examined, along with factors shaping the poetic articulation of the feminine in the Middle Ages. Part I sets out the background material which provides the context for the close readings of Parts II and III. Since the framework within which Chaucer's female characters speak is poetic, the first chapter is concerned with contemporary views about how poetic meaning is produced: what is the status of the author? How does the author read - and rewrite - his or her sources? Which rhetorical conventions govern literary representation, and how is the literary text justified? Part I also considers why rhetoric should be an issue as regards women in the Middle Ages, and what modes of signifying are available to women in social, spiritual and literary contexts. Perspectives on appropriate female behaviour and discourse are gained through an examination of the rhetorical traction, works of devotional and didactic instruction, and the conventions of fin'amor. Parts II and III present a close reading of Chaucer's poetry. The readings are informed by the perspectives outlined in Part I, and by modern literary theories, and involve some assessment of the applicability of recent theory to Chaucer's poetry. The Legend of Good Women and Troilus and Criseyde are both seen as vitally concerned with poetic practice and theory, and with the poetic representation of female characters. The poet's representation of the heroines in the course of the Legend provides a critique of the conception of poetry articulated by the god of Love in the Prologue. The hermeneutical and representational difficulties that the poet of the Troilus experiences with his poem are intimately linked with his treatment of Criseyde. The thesis considers the intersection between poetics and the poetic representation of the feminine.